A turn to practice: Core practices in social studies teacher education. (1st October 2020) - Dinkelman, Todd; Cuenca, Alexander
ABSTRACT: There is growing momentum in teacher education to organize the preparation of teachers around "core practices." Advocates call for identifying discipline-oriented, research-based teaching moves associated with student learning and then shifting teacher education pedagogies and programs toward preparing beginning teachers to implement these moves in classroom and school settings. This study examines core practices as a recent reform impulse in teacher education practice. The authors explore a growing literature on core practices to generate both conceptual and practice-based responses with special attention to social studies teacher education. By leveraging two vignettes of "on-the-ground" social studies teacher education, the authors discuss questions and issues about taking core practices into the murky, diverse, and complex practice spaces of social studies teacher education and extend the conversation about what this set of reform ideas might mean for social studies education.